Chemokines and Chemokine Receptors: New Targets for Cancer Immunotherapy - Mollica Poeta, Valeria; Massara, Matteo; Capucetti, Arianna; Bonecchi, Raffaella (Frontiers in Immunology, 2019)
Immunotherapy is a clinically validated treatment for many cancers to boost the immune system against tumor growth and dissemination. Several strategies are used to harness immune cells: monoclonal antibodies against tumor antigens, immune checkpoint inhibitors, vaccination, adoptive cell therapies (e.g., CAR-T cells) and cytokine administration. In the last decades, it is emerging that the chemokine system represents a potential target for immunotherapy. Chemokines, a large family of cytokines with chemotactic activity, and their cognate receptors are expressed by both cancer and stromal cells. Their altered expression in malignancies dictates leukocyte recruitment and activation, angiogenesis, cancer cell proliferation, and metastasis in all the stages of the disease. Here, we review first attempts to inhibit the chemokine system in cancer as a monotherapy or in combination with canonical or immuno-mediated therapies. We also provide recent findings about the role in cancer of atypical chemokine receptors that could become future targets for immunotherapy.